ASEAN in the Age of Anti-Globalization: Compartmentalized Regionalism(s) and Three Trajectories - Shofwan Al Banna Choiruzzad (IKAT: The Indonesian Journal of Southeast Asian Studies, 2017)
This essay attempts to examine the prospect of ASEAN integration in the age of anti-globalization by understanding ASEAN as a compartmentalized regionalism. It argues that discussions on the prospect of ASEAN are actually discussions on the trajectories of two separate regional projects: economic regionalism and political security regionalism. It must be noted that we often have difficulties separating the two because their evolution has so far been marked by centripetal movement towards liberal tradition in the two regional projects. However, since we are entering the age of anti-globalization, this is changing. To make an educated guess on the future of ASEAN regionalism(s), I argue that we should focus our attention to three main indicators: (1) Structural: will the international system be cooperative or competitive multipolar system? (2) National elite orientation: will the liberal elites and technocracy in ASEAN countries remain liberal, or will nationalist elites take charge?; and (3) Public sentiment: how big is the positive or negative sentiment towards economic liberalization?